Perilaku Hidup Bersih dan Sehat (PHBS) Sebagai Upaya Pencegahan Stunting di Desa Sarani Matani Kecamatan Tombariri Kabupaten Minahasa - Gunawan, Levitt; Audriano Kalundang; Axl Ferdy Worotitjan; Berkatia Maryelia Sinay; Beylia Malaihang; Crysthania Cleryne Pianaung; Diana Febrianti Tilli; Stefani Sofia Sagai; Stefania Anita Sambuaga; Yunita Siske Wentuk; Yolanda Trivena Tumbel; Megita Syalom Otta; Meri Mamantung; Ivana Papuanita Bagre; Indra Dewi Keribo (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Stunting is not only a nutritional problem but also a problem of clean and healthy living behavior. Unclean and healthy living patterns such as lack of awareness of cleaning the living environment, river pollution with garbage and animal feces, unclean sanitation are still found in people's lives in general, this is motivated by a lack of understanding of Clean and Healthy Living Behavior (PHBS). This research was conducted with the aim of being able to provide education and explanation or socialization about PHBS and stunting problems so that the community gets a good understanding related to a healthy lifestyle. The research method used in this paper is the participatory observation method, in which researchers closely observe a group of people/culture/community and their habits. The results of this study show that the community's understanding of PHBS has become better and more comprehensive and is the first step that will continue to be developed in efforts to deal with stunting in terms of a healthy lifestyle.